Analysis of the supporting attitude of Changsha-Zhuzhou-Xiangtan residents toward the interactive development of sports events and urban tourism - Li, Lizhi; Liang, Jiang (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study investigated the supportive attitudes of residents in Changsha-Zhuzhou-Xiangtan toward the interactive development of sports events and urban tourism. The study employed a survey-based quantitative method, with a total of 115 residents participating. The survey assessed the impact through three key dimensions: economic impact, tourism image impact, and spatial impact, comprising 12 factors. The results indicated strong support among residents for the idea that sports events can generate economic benefits, enhance the urban tourism image, and stimulate spatial development. Sports events impact the tourism economy, improve the city’s image, and create a cultural ambiance, fostering mutual growth between sports and tourism in the region. Pearson correlation analysis revealed a significant positive relationship (p<0.05) between sports events and tourism-related income, including transportation, dining, and accommodation. Residents’ cognitive attitudes are explained by 35.5% of these factors, while 83.8% of their willingness to support the events is attributed to the same factors. Local governments should support distinctive sports events, optimize tourism resources, and enhance infrastructure to stimulate rapid economic growth.